No effect of recombination on the efficacy of natural selection in primates - Bullaughey, Kevin; Przeworski, Molly; Coop, Graham

(untitled) (Genome Research, 2008)
Population genetic theory suggests that natural selection should be less effective in regions of low recombination, potentially leading to differences in rates of adaptation among recombination environments. To date, this prediction has mainly been tested in Drosophila, with somewhat conflicting results. We investigated the association between human recombination rates and adaptation in primates, by considering rates of protein evolution (measured by dN/dS) between human, chimpanzee, and rhesus macaque. We found no correlation between either broad- or fine-scale rates of recombination and rates of protein evolution, once GC content is taken into account. Moreover, genes in regions of very low recombination, which are expected to show the most pronounced reduction in the efficacy of selection, do not evolve at a different rate than other genes. Thus, there is no evidence for differences in the efficacy of selection across recombinational environments. An interesting implication is that indirect selection for recombination modifiers has probably been a weak force in primate evolution.